Nuclear Methods for Immune Cell Imaging: Bridging Molecular Imaging and Individualized Medicine. (17th January 2023) - Heo, Gyu Seong; Diekmann, Johanna; Thackeray, James T.; Liu, Yongjian
Abstract : Inflammation is a key mechanistic contributor to the progression of cardiovascular disease, from atherosclerosis through ischemic injury and overt heart failure. Recent evidence has identified specific roles of immune cell subpopulations in cardiac pathogenesis that diverges between individual patients. Nuclear imaging approaches facilitate noninvasive and serial quantification of inflammation severity, offering the opportunity to predict eventual outcome, stratify patient risk, and guide novel targeted molecular therapies against specific leukocyte subpopulations. Here, we will discuss the established and emerging nuclear imaging methods to label and track exogenous and endogenous immune cells, with a particular focus on clinical situations in which targeted molecular inflammation imaging would be advantageous. The expanding options for imaging inflammation provide the foundation to bridge between molecular imaging and individual therapy.